PENGARUH LEVERAGE, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP KUALITAS LABA - Fatikatun Nisa’ Salsabillah; Muhammad Aufa (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2023)
This study aims to determine and test the effect of leverage, liquidity, and company size on earnings quality. The sampling technique used was purposive sampling with a total sample from 49 consumer sector manufacturing companies listed on the Indonesia Stock Exchange (IDX). This type of research is quantitative research with secondary data in the 2019-2021 observation year. Data analysis techniques in this study used descriptive statistical analysis, classical assumption test and multiple linear regression analysis using the IBM SPSS Statistics 26 program. The results of this study indicate that the leverage variable has a significant effect on earnings quality. While the variables of liquidity and company size do not have a significant effect on earnings quality